Hammersmith Infant Neurological Examination and long-term cognitive outcome in children born very preterm - Uusitalo Karoliina; Haataja Leena; Nyman Anna; Lehtonen Tuomo; Setänen Sirkku; PIPARI Study Group (WILEY, 2022)
Aim: To study the association between the Hammersmith Infant Neurological Examination (HINE) at age 2 years and neurocognition at age 11 years in children born very preterm. We hypothesized that the HINE at 2 years would be associated with neurocognition, that is, neurological, motor, and cognitive outcomes at 11 years.
Method: A total of 174 children (mean gestational age 29.0wks, SD 2.7; minimum 23.0, maximum 35.9; 95 [55%] males, 79 [45%] females) born very preterm (birthweight ≤1500g/gestational age <32wks), were included in a prospective cohort recruited from 2001 to 2006 in Turku, Finland. The HINE was performed at 2 years' corrected age. Neurocognition at 11 years was assessed with the Touwen neurological examination, Movement Assessment Battery for Children, Second Edition (MABC-2), and full-scale IQ (Wechsler Intelligence Scale for Children, Fourth Edition).
Results: The HINE global score was associated with the results of the Touwen neurological examination (odds ratio [OR]=0.9, 95% confidence interval [CI] 0.8-0.9, p=0.001), MABC-2 (β=1.4, 95% CI 0.7-2.2, p<0.001), and full-scale IQ (β=1.2, 95% CI 0.8-1.7, p<0.001), even when adjusted. When children with cerebral palsy (CP) were excluded, the HINE was still associated with full-scale IQ (unadjusted β=1.2, 95% CI 0.3-2.1, p=0.01).
Interpretation: A higher HINE global score at 2 years was associated with better general intelligence at 11 years even in children without CP. The HINE may be a useful tool to detect children at risk for later cognitive impairment. What this paper adds A Hammersmith Infant Neurological Examination (HINE) global score at 2 years was associated with long-term neurocognitive function. Severe cognitive impairment was significantly more common in 11-year-old children with complex minor neurological dysfunction compared to typically developing children. The HINE performed at 2 years detects risks of cognitive impairment at 11 years in children born very preterm. A higher HINE score at 2 years was associated with better general intelligence at 11 years.